A Rare Case of Burkholderia Cepacia Complex Septicemia in a Newborn (KYAMC Journal, 2022)
Burkholderia cepacia complex (Bcc) has rarely been reported to cause sepsis in newborns. A case in a newborn male was reported in a tertiary hospital in northern part of Bangladesh Khwaja Yunus Ali Medical College and Hospital, Sirajganj. The baby was born to a preeclamptic mother. He was quite well after a normal vaginal delivery. After 6 days, the baby was admitted to neonatal ward on complaint of dyspnea and fever. Antibiotic therapy was begun after samples for hemocultures were obtained with the suspicion of sepsis according to the clinical and laboratory findings. At the same time, he had a respiratory distress and grunting along with the absence of crying for a prolonged period of time. He was jaundiced. Blood culture revealed the presence of Bcc. The patient was sent to the Intensive Care Unit for resuscitation. Antibiotic susceptibility test of the blood specimen showed sensitivity to amikacin, ceftazidime, trimethoprim-sulfamethoxazole, meropenem and levofloxacin. Symptoms improved with medical support along with antimicrobial therapy. This case highlights the importance of diagnostic blood culture of an acute sepsis condition to obtain a specific etiological diagnosis and management. KYAMC Journal Vol. 13, No. 03, October 2022: 181-182